Perencanaan Sistem Pembelajaran PAI Berbasis Human-Centered Learning dalam Meningkatkan Kualitas Pembelajaran - Hakim, Abd. (LP3M STITNU AL HIKMAH MOJOKERTO, 2025)
The development of modern educational paradigms requires transformation in the learning planning system so that it becomes more oriented toward the needs of students. One of the approaches that has developed in the field of education is the human-centered learning approach, which is a learning model that places students as the center of the learning process. This approach has become increasingly relevant in the context of Islamic Religious Education (PAI) because the primary objective of Islamic education is not only to emphasize cognitive aspects but also to foster character development, moral values, and the spirituality of students. This study aims to analyze the concept of planning the Islamic Religious Education learning system based on human-centered learning and its implications for improving the quality of learning. This research uses a qualitative method with a library research approach. The data were obtained from various literature sources such as books, scientific journals, and academic documents relevant to the research topic. The results of the study indicate that the implementation of human-centered learning-based learning planning can increase students' active participation, strengthen their understanding of Islamic values, and create a more dialogical and reflective learning process. In addition, this approach is also able to encourage the holistic development of students' potential, including intellectual, emotional, and spiritual aspects. Therefore, planning an Islamic Religious Education learning system based on human-centered learning can be an important strategy in improving the quality of Islamic Religious Education learning in educational institutions. Abstrak Perkembangan paradigma pendidikan modern menuntut adanya transformasi dalam sistem perencanaan pembelajaran agar lebih berorientasi pada kebutuhan peserta didik. Salah satu pendekatan yang berkembang dalam dunia pendidikan adalah pendekatan human-centered learning, yaitu model pembelajaran yang menempatkan peserta didik sebagai pusat dari proses pembelajaran. Pendekatan ini menjadi semakin relevan dalam konteks Pendidikan Agama Islam (PAI) karena tujuan utama pendidikan Islam tidak hanya menekankan pada aspek kognitif, tetapi juga pada pembentukan karakter, nilai moral, dan spiritualitas peserta didik. Penelitian ini bertujuan untuk menganalisis konsep perencanaan sistem pembelajaran PAI berbasis human-centered learning serta implikasinya terhadap peningkatan kualitas pembelajaran. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kepustakaan. Data diperoleh dari berbagai sumber literatur seperti buku, jurnal ilmiah, serta dokumen akademik yang relevan dengan topik penelitian. Hasil penelitian menunjukkan bahwa penerapan perencanaan pembelajaran berbasis human-centered learning dapat meningkatkan partisipasi aktif peserta didik, memperkuat pemahaman nilai-nilai keislaman, serta menciptakan proses pembelajaran yang lebih dialogis dan reflektif. Selain itu, pendekatan ini juga mampu mendorong pengembangan potensi peserta didik secara holistik, baik dalam aspek intelektual, emosional, maupun spiritual. Dengan demikian, perencanaan sistem pembelajaran PAI berbasis human-centered learning dapat menjadi salah satu strategi penting dalam meningkatkan kualitas pembelajaran Pendidikan Agama Islam di lembaga pendidikan.